2016
DOI: 10.1021/acs.jmedchem.5b00608
|View full text |Cite
|
Sign up to set email alerts
|

Development of 3,5-Dinitrobenzylsulfanyl-1,3,4-oxadiazoles and Thiadiazoles as Selective Antitubercular Agents Active Against Replicating and Nonreplicating Mycobacterium tuberculosis

Abstract: Herein, we report the discovery and structure−activity relationships of 5-substituted-2-[(3,5-dinitrobenzyl)sulfanyl]-1,3,4-oxadiazoles and 1,3,4-thiadiazoles as a new class of antituberculosis agents. The majority of these compounds exhibited outstanding in vitro activity against Mycobacterium tuberculosis CNCTC My 331/88 and six multidrug-resistant clinically isolated strains of M. tuberculosis, with minimum inhibitory concentration values as low as 0.03 μM (0.011−0.026 μg/ mL). The investigated compounds ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 44 publications
6
86
0
1
Order By: Relevance
“…Furthermore, studies were performed which attempted to characterize the possible target of the compounds. In vitro studies suggested that compounds ( 1 ) and ( 2 ) could act inhibiting the synthesis of nucleic acids [13]. The same research group has reported a new series of 3,5-dinitrophenyl 1,3,4-oxadiazole-2-thiols and tetrazole-5-thiols as promising antitubercular agents.…”
Section: Antituberculosis Compoundsmentioning
confidence: 99%
“…Furthermore, studies were performed which attempted to characterize the possible target of the compounds. In vitro studies suggested that compounds ( 1 ) and ( 2 ) could act inhibiting the synthesis of nucleic acids [13]. The same research group has reported a new series of 3,5-dinitrophenyl 1,3,4-oxadiazole-2-thiols and tetrazole-5-thiols as promising antitubercular agents.…”
Section: Antituberculosis Compoundsmentioning
confidence: 99%
“…Structure activity relationship studies demonstrated that the 3,5 dinitro phenyl fragment to be the crucial in conferring anti-mycobacterial activity. [138][139][140] Any changes in position of the dinitro group led to the loss or several fold decrease of anti-TB activity. An AMES test indicated these nitro group-containing compounds have no mutagenic activity.…”
Section: The Promising Molecules and Natural Productsmentioning
confidence: 99%
“…Among five membered heterocyclic compounds, azoles such as oxadiazoles, thiadiazoles, and triazoles are an indispensable class of heterocyclic family to display diverse pharmaceutical as well as biological applications . 1,3,4‐Oxadiazole and their derivatives presents antioxidant antimicrobial and anticonvulsant properties.…”
Section: Introductionmentioning
confidence: 99%